Al-Rabghuzi's the Stories of the prophets : Qiṣaṣ al-anbiyā' : an Eastern Turkish version - Rabghuziĭ, Nosiruddin Burḣonuddin, active 13th century-14th century. (Middle East and Islamic Studies E-Books Online, Collection 2015, ISBN: 9789004287464., 2015)
A first edition of The Stories of the Prophets , written in Khwarezmian Turkish by the judge ( qāḍī ) Rabghūzī and completed in 1311, was published in 1995 by a group of authors. For the second edition H.E. Boeschoten and J. O'Kane have thoroughly revised both the text edition and the translation volume on the basis of additional manuscripts and reviews of the first edition. The Stories of the Prophets ( Qiṣaṣ al-Anbiyā' ) is a traditional genre in Islamic literature. Such a work contains the res gestae of the biblical prophets and stories about other personalities and peoples up to the birth of the Prophet Muḥammed. Exceptionally, Rabghūzī's Stories also contains a sizable account of the life of Muḥammed and his family. The work is a fundamental source both for Turkic linguistics and for Islamic Studies.